Reactive epoxy-functionalized thin films by a pulsed plasma polymerization process - Thierry, Benjamin (Langmuir : the ACS journal of surfaces and colloids, 2008)
A novel plasma functionalization process based on the pulsed plasma polymerization of allyl glycidyl ether is reported for the generation of robust and highly reactive epoxy-functionalized surfaces with well-defined chemical properties. Using a multitechnique approach including X-ray photoelectron spectroscopy (XPS), time-of-flight secondary ion mass spectrometry (ToF-SIMS), infrared spectroscopy (FT-IR), atomic force microscopy (AFM) and ellipsometry, the effect of the plasma deposition parameters on the creation and retention of epoxy surface functionalities was characterized systematically. Under optimal plasma polymerization conditions (duty cycle: 1 ms/20 ms and 1 ms/200 ms), reactive uniform films with a high level of reproducibility were prepared and successfully used to covalently immobilize the model protein lysozyme. Surface derivatization was also carried out with ethanolamine to probe for epoxy groups. The ethanolamine blocked surface resisted nonspecific adsorption of lysozyme. Lysozyme immobilization was also done via microcontact printing. These results show that allyl glycidyl ether plasma polymer layers are an attractive strategy to produce a reactive epoxy functionalized surface on a wide range of substrate materials for biochip and other biotechnology applications